Do works councils raise or lower firm productivity? - Olaf Hübler (IZA World of Labor, 2015)
The German model of co-determination (Mitbestimmung) with works councils, in which workers are involved in the management of a company, was a role model for other countries for many years. However, since the 1990s the appeal of works councils has been declining, to the extent that now even employees are sometimes voting against representation. This was recently demonstrated by workers at the Volkswagen factory in Chattanooga, Tennessee, who voted against union representation. An important question for firms and for policymakers is whether the adoption of a works council has a positive influence on a firm's productivity and what the consequences are for a firm's profits.
Keywords: D2; D7; D83; J21; J31; J5; 330; works councils; productivity; employment; wages and profit effects